Five-Year Antibody Persistence Following a Japanese Encephalitis Chimeric Virus Vaccine (JE-CV) Booster in JE-CV–Primed Children in the Philippines. (9th January 2018) - Capeding, Maria Rosario; Alberto, Edison R; Bouckenooghe, Alain; Laot, Thelma M; Chansinghakul, Danaya; Monfredo, Céline; Machabert, Tifany; Feroldi, Emmanuel
Abstract : This study shows that the immune response elicited by a Japanese encephalitis chimeric virus vaccine (JE-CV) booster in JE-CV–primed children in the Philippines induces long-lasting protection, and further supports the benefit of a booster irrespective of when primary vaccination was administered. Abstract: We assessed antibody persistence following booster vaccination with a Japanese encephalitis chimeric virus vaccine (JE-CV; IMOJEV) in JE-CV–primed children. In an open phase 3 trial, 349 children in the Philippines, who received JE-CV 2 years previously, received a booster dose. JE neutralizing antibody titers were assessed (50% plaque reduction neutralization test) annually for up to 5 years after booster vaccination. Seroprotection rates (percentage of children with titers ≥10 [1/dil]) and geometric mean titers (GMTs) were, respectively, 98.2% and 161 after 5 years. JE-CV booster induced long-lasting anamnestic immune response in JE-CV–primed children, with high seroprotection rates and GMTs over the accepted threshold for serological protection (10 [1/dil]). Clinical Trials Registration: NCT01190228.